Analysis Of The Influence Of The Mutanaqisah Musyarakah Agreement On The Marketing Process On Customer Purchasing Decisions In The Indonesia Eximbank Syariah Business Unit - Fadhil Kefee Prasetyo; Murwanto SIgit (Cita konsultindo, 2024)
The study aims to analyze the influence of Musyarakah Mutanaqisah on marketing processes on customer purchasing decisions in the sharia business unit of Indonesia Eximbank Jakarta branch. The method used in this research is using observation and interview methods. The observation process was carried out during the internship and the interview process was conducted against 6 respondents who were managers, employees, and customers from Indonesia Eximbank. The interview questions were made based on the observations during internships related to research topics. The results of this study show that there is an influence of Musyarakah Mutanaqisah (MMQ) covenant on the decision of customer purchase in the shariah business unif of Indonesia Eximbank. This is due to the advantages of the Musyarakah Mutanaqisah covenant which drives the purchasing factors of financing products in Indonesia Eximbank.